Demographic Challenges in Non-metropolitan Western Australia: Community Development Strategies in a Neo-liberal Economic Environment. - McKenzie, Fiona Haslam (2004)
Many communities throughout non-metropolitan Australia are experiencing change; changes in service delivery and infrastructure, changes in traditional industries and the industry mix, changes in the demographic and cultural mix of local residents and changes in local and political leadership. Some communities, particularly those in broadacre agricultural areas have experienced significant depopulation and struggle to remain viable, while others, particularly those on the coast, have experienced unprecedented population growth, creating pressure on the local economy, housing, infrastructure, long held traditions and social networks. It would appear that both types of communities often feel threatened and have grappled with change from a number of perspectives; some with more success than others.In the proposed paper, I will seek to understand why some communities have coped with change better than others and identify the inhibitors and facilitators enabling the optimisation of change for sustainable regional development. Related to this, is the need for greater exploration of the new styles of community leadership and strategies for continued commitment to capacity building and the creation of social capital in non-metropolitan areas of Australia, particularly those experiencing change. The economic, social and environmental implications will be viewed as a set of issues that are indivisible from other policy pursuits.It is proposed that two regions will be examined, one that has been threatened by depopulation, such as the Central Wheatbelt of Western Australia, and the other to be investigated will be one that has experienced significant coastal growth, such as the Capes region of South West, Western Australia. The coping mechanisms and the regional development strategies of each will be compared and contrasted. An anticipated outcome would be strategies that encourage greater collaboration between the policy makers, authorities and stakeholders, thereby enhancing the capabilities and capacities.